2003
DOI: 10.1021/ie020401i
|View full text |Cite
|
Sign up to set email alerts
|

Two Advanced Models for the Kinetics of the Variation of the Tar Composition in Its Catalytic Elimination in Biomass Gasification

Abstract: Biomass gasification in fluidized beds generates tar that can be effectively eliminated with catalysts located downstream from the biomass gasifier. Some previously obtained results from such catalytic tar elimination were hard to be understood because the tar was considered as only one or two lumps. For this reason, in this work, tar is considered in two ways:  (i) as being composed of six different lumps and (ii) as a continuous mixture. For these studies, tar was sampled before and after two catalytic beds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 36 publications
(52 reference statements)
0
60
0
Order By: Relevance
“…8) indicated that coke was accumulated on both supports in significant amounts, strongly suggesting that deactivation was essentially caused by the carbonaceous species formed during decomposition of phenol on the metal oxides. In the case of the catalytic steam reforming of phenathrene [20], opening of the aromatic rings has been proposed as the first step in the formation of ring radicals which further react or condense to lead to coke on the catalyst surface. This aromatic ring-opening mechanism could also be applied in our phenol steam reforming case.…”
Section: Discussionmentioning
confidence: 99%
“…8) indicated that coke was accumulated on both supports in significant amounts, strongly suggesting that deactivation was essentially caused by the carbonaceous species formed during decomposition of phenol on the metal oxides. In the case of the catalytic steam reforming of phenathrene [20], opening of the aromatic rings has been proposed as the first step in the formation of ring radicals which further react or condense to lead to coke on the catalyst surface. This aromatic ring-opening mechanism could also be applied in our phenol steam reforming case.…”
Section: Discussionmentioning
confidence: 99%
“…Another method is to consider tar as a single lump component of the type C x H y O z or with an unspecified formula. To improve the single lump model, Corella [26] proposed two advanced kinetic models for catalytic tar removal in õbiomass gasification processes, considering tar composed of six different lumps and as a continuous mixture. Tables of kinetic constants of different literature sources are presented in [27,28,10,9].…”
Section: Kinetics Of the Tar Steam Reforming Reactionmentioning
confidence: 99%
“…Since kinetic constants for one-or two lump models are specific for a given gasifier, feedstock and process [26], the kinetic values have to be adapted to the experimental conditions. A comparison of literature values, considering data determined under experimental conditions similar to the setup described in Section 2, indicates comparable values for the Activation energy E app in different literature sources.…”
Section: Kinetics Of the Tar Steam Reforming Reactionmentioning
confidence: 99%
“…In their work, a simple kinetic model is used to describe the overall tar elimination network. Corella et al 23,24 conducted extensive studies on tar elimination reactions and kinetics. Figure 36 is a summary of E app values found by several authors with different catalysts.…”
Section: Summary Of Literature Findingsmentioning
confidence: 99%